On the relationship between metabolic capacities and in vivo viscoelastic properties of the liver - Shahryari, Mehrgan; Keller, Sarah; Meierhofer, David; Wallach, Iwona; Safraou, Yasmine; Guo, Jing; Marticorena Garcia, Stephan R.; Braun, Jürgen; Makowski, Marcus R.; Sack, Ingolf; Berndt, Nikolaus (Frontiers in Bioengineering and Biotechnology, 2023)
The liver is the central metabolic organ. It constantly adapts its metabolic capacity to current physiological requirements. However, the relationship between tissue structure and hepatic function is incompletely understood; this results in a lack of diagnostic markers in medical imaging that can provide information about the liver’s metabolic capacity. Therefore, using normal rabbit livers, we combined magnetic resonance elastography (MRE) with proteomics-based kinetic modeling of central liver metabolism to investigate the potential role of MRE for predicting the liver’s metabolic function in vivo. Nineteen New Zealand white rabbits were investigated by multifrequency MRE and positron-emission tomography (PET). This yielded maps of shear wave speed (SWS), penetration rate (PR) and standardized uptake value (SUV). Proteomic analysis was performed after the scans. Hepatic metabolic functions were assessed on the basis of the HEPATOKIN1 model in combination with a model of hepatic lipid-droplet metabolism using liquid chromatography–mass spectrometry. Our results showed marked differences between individual livers in both metabolic functions and stiffness properties, though not in SUV. When livers were divided into ‘stiff’ and ‘soft’ subgroups (cutoff SWS = 1.6 m/s), stiff livers showed a lower capacity for triacylglycerol storage, while at the same time showing an increased capacity for gluconeogenesis and cholesterol synthesis. Furthermore, SWS was correlated with gluconeogenesis and PR with urea production and glutamine exchange. In conclusion, our study indicates a close relationship between the viscoelastic properties of the liver and metabolic function. This could be used in future studies to predict non-invasively the functional reserve capacity of the liver in patients.